Mixed Pseudo-orthogonal Frequency Coding for SAW RFID Tags - XU, Mengru; XIAO, Xia; YUAN, Qing; ZONG, Yong (Archives of Acoustics, 2018)
A mixed pseudo-orthogonal frequency coding (Mixed-POFC) structure is proposed as a new spreadspectrum technique in this paper, which employs frequency and time diversity to enhance tag properties and balances the spectrum utilization and code diversity. The coding method of SAW RFID tags in this paper uses Mixed-POFC with multi-track chip arrangements. The cross-correlation and auto correlation of Mixed-POFC and POFC are calculated to demonstrate the reduced overlap between the adjacent center frequencies with the Mixed-POFC method. The center frequency of the IDT and Bragg reflectors is calculated by a coupling of modes (COM) module. The combination of the calculation results of the Bragg reflectors shows that compared with a 7-chip POFC, the coding number of a 7-chip Mixed-POFC is increased from 120 to 144 with the same fractional bandwidth of 12%. To demonstrate the validity of Mixed-POFC, finite element analysis (FEA) technology is used to analyze the frequency characteristics of Mixed-POFC chips. The maximum error between designed frequencies and simulation frequencies is only 1.7%, which verifies that the Mixed-POFC method is feasible.